The labour market policy in the EU - Ewa Rollnik-Sadowska; Edyta Dabrowska; Britta Luedeke; Doris Wiethoelter (Institute of Economic Research (IER), 2017)
In the era of demographic changes and need for rationalization of public expenditure, the European Union social policy promotes the activation approach. In addition, there can be noticed a growing importance of increasing the efficiency of public policies. The authors are presenting the main theoretical assumptions concerning efficiency as well as classification of methods for measuring of efficiency of labour market policies. Moreover, the EU countries are classified in clusters according to their level of expenditure on different categories of LMP. The paper is based on critical analysis of literature as well as analysis of secondary research findings. The cross-country labour market situation in the EU is based on the analysis of the Eurostat data by the k-means method. There is a need to work out a complex evaluation of labour market policies in the EU to provide comparative analysis of the EU countries (or groups of countries). It would allow determining the level of development of the country in terms of the efficiency of labour market policies.The EU countries with the best labour market situation represent diverse levels of LMP expenditure.
Keywords: J01; J08; J11; J24; J88; 330; labour market policy; efficiency; LMP expenditure; clusters of the European Un-ion countries